Transformasi BUMG Maju Jaya Berbasis Modal Sosial, Gampong Peunaga Pasi, Aceh Barat - Titis Rahayu Trisnawati; Afrizal Tjoetra; Arfriani Maifizar; Ikhsan Ikhsan (Jurnal Community, 2025)
Gampong-Owned Enterprises (BUMG) are expected to become economic institutions that lead to gampong independence through community empowerment. However, the condition of the development of BUMG is far from the government's expectations. This study aims to analyze the role of social capital in the management of BUMG Maju Jaya. This study uses a qualitative method with a case study approach. The results of this study illustrate that the success of BUMG Maju Jaya is not only determined by financial capital, but also by the strength of social capital that is integrated in three main dimensions, namely bonding social capital (internal solidarity), bridging social capital (networks between groups), and linking social capital (access to external resources). Social capital plays a key catalyst that drives active community participation, builds trust in BUMG managers, and strengthens internal and external social networks. Social capital has transformed BUMG from a mere business entity to a social-based economic institution that empowers the community. The results of this research are expected to be a reference for other BUMG managers in reviving gampong economic institutions.